Review of: "Why Native Language Secrecy No Longer Works in Modern Warfare: The Case of North Koreans in the Russo-Ukrainian War" - Sorokina, Anastasia (Qeios, 2025)
Keywords: Ancient history; Geography; History; Law; Linguistics; Philosophy; Political science; Secrecy; Ukrainian; dept.wll

Turning to returnees - Schmitt, Elena (Linguistic Approaches to Bilingualism, 2025)
Keywords: dept.wll

Humanistic Education: A Collection of Reflective Essays - Narvaez, George (Independently published, 2025)
Humanistic Education: A Collection of Reflective Essays by George Narvaez is a compelling anthology that bridges classical philosophy, modern educational theory, and personal reflection. Drawing on the author’s graduate studies at Harrison Middleton University, these twenty essays offer a deep dive into the evolution of human thought on education, knowledge, and the art of learning.This book is ideal for readers interested in the humanities, education, philosophy, or self-directed learning. It engages with timeless questions:What does it mean to “know” something?How is knowledge constructed and communicated?How can education empower individuals and communities?Inside this collection, you will explore:✔️ The foundational philosophies of Plato, Aristotle, Augustine, and Aquinas✔️ Modern insights from William James, John Dewey, and Benjamin Franklin✔️ The evolution of rhetoric and epistemology across history✔️ The relationship between language, culture, and cognition✔️ The author's transformative journey through educationEach essay combines academic rigor with accessible language, offering readers a path to understand how classical theories of liberal education connect with contemporary learning practices. From the “education of the hemispheres” in William James’s psychology to the experiential learning of Franklin and Dewey, the author shows that learning is not just about absorbing information—it’s about transforming the way we live, communicate, and understand ourselves and others.Key themes include:Rhetoric as a tool for empowermentEpistemology as a process of inquiryCivic responsibility through educationPersonal growth through humanistic reflectionWhether you're an educator, student, scholar, or lifelong learner, Humanistic Education is a thought-provoking guide to the intellectual traditions that continue to shape our educational ideals.Start your journey through the minds of history’s greatest thinkers—and reflect on your own learning path.

Bilingual autobiographical memory: unveiling the significance of memories encoded in multiple languages - Sorokina, Anastasia (Multilingua, 2025)
Keywords: Autobiographical memory; Cognitive psychology; Cognitive science; Computer science; Linguistics; Philosophy; Psychology; Recall; bilingual autobiographical memory; dept.wll; memory phenomenology; mixed memories; peer-reviewed